Analytical network process based on BOCR analysis as an approach for designing a foreign direct investment policy - Šimelytė, Agnė; Peleckis, Kęstutis; Korsakienė, Renata (Journal of Business Economics and Management, 2014)
Foreign direct investment is significantly important for the emerging market countries or countries in transition. Scientific literature provides plenty of evidence that FDI may have both negative and positive influence on economic growth. However, research proves that just specific type of FDI may bring benefit to the host country. Thus, a targeted FDI policy is essential for directing foreign capital into problematic business areas or regions. The goal of the article is to propose a complex targeted FDI policy, the employment of which would give benefits to the host country and achieve its strategic goals. Benefit-opportunities-costs-risks analysis and analytic network process method are used for the empirical research. Final results reveal that Lithuania, attracting FDI into research and development area, gains great benefits and exploits opportunities. At the same time, the highest costs might be generated while implementing a FDI policy in this area. A FDI policy towards service sectors would cause the least amount of risks. These results are significant for academics as the basis for further research, and decisions-makers as guidance for the development of the national FDI policy.